Enhanced aerodynamic and mechanical performance of double-rotor wind turbines via a one-way fluid-structure interaction analysis - Yaru Yang; Wenhua Zhuang; Ping Yuan; Rong Yuan; Jing Yuan; Fengyun Sun; Yongxu Hu (PLoS ONE, 2026)
Double-rotor wind turbines (DRWTs) have emerged as a promising alternative to conventional single-rotor wind turbines (SRWTs). This study proposes a novel DRWT equipped with a differential planetary gearbox and compares it with a geometrically equivalent SRWT through Computational Fluid Dynamics (CFD) and One-way Fluid-Structure Interaction (FSI) -based simulations under varying wind conditions. Dynamic meshing, six-degree-of-freedom motion, and user-defined stochastic wind loading were incorporated into the numerical framework. Compared with the SRWT, the DRWT shows 4.2% faster wake-velocity recovery in the z4 plane and a 28.35% reduction in time-varying peak blade stress compared to the equivalent ss-SRWT. Results demonstrate that the DRWT exhibits superior aerodynamic efficiency and mechanical performance, despite its more intricate structure. These findings contribute valuable insights for the operational control and structural design optimization of DRWTs.